2009
DOI: 10.1186/1478-811x-7-22
|View full text |Cite
|
Sign up to set email alerts
|

Function, regulation and pathological roles of the Gab/DOS docking proteins

Abstract: Since their discovery a little more than a decade ago, the docking proteins of the Gab/DOS family have emerged as important signalling elements in metazoans. Gab/DOS proteins integrate and amplify signals from a wide variety of sources including growth factor, cytokine and antigen receptors as well as cell adhesion molecules. They also contribute to signal diversification by channelling the information from activated receptors into signalling pathways with distinct biological functions. Recent approaches in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
228
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 160 publications
(234 citation statements)
references
References 240 publications
(436 reference statements)
6
228
0
Order By: Relevance
“…Overexpression of p35-GAB1, itself activated by HGF/SF, was capable of causing the subsequent downstream activation of the PI3K-AKT pathway as well as cell migration and resistance to apoptotic stress. On the other hand, p35-GAB1, in agreement with the loss of the C-terminal part of GAB1, was not capable to recruit SHP2 any more, and its overexpression in cells was associated with a reduced activation of the RAS-ERK pathway, as expected for the role of SHP2 in GAB1 signaling (7,8,14,15). Taken together, these data indicate that the caspase cleavage of the GAB1 docking adaptor protein can maintain HGF/SF-induced cell survival/resistance to apoptosis (Fig.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Overexpression of p35-GAB1, itself activated by HGF/SF, was capable of causing the subsequent downstream activation of the PI3K-AKT pathway as well as cell migration and resistance to apoptotic stress. On the other hand, p35-GAB1, in agreement with the loss of the C-terminal part of GAB1, was not capable to recruit SHP2 any more, and its overexpression in cells was associated with a reduced activation of the RAS-ERK pathway, as expected for the role of SHP2 in GAB1 signaling (7,8,14,15). Taken together, these data indicate that the caspase cleavage of the GAB1 docking adaptor protein can maintain HGF/SF-induced cell survival/resistance to apoptosis (Fig.…”
Section: Discussionmentioning
confidence: 57%
“…It contains the GAB1-MBD and has conserved one of the two GRB2 binding motifs (aa 516 -525) and all three SH2 binding sites for p85-PI3K but has lost the C-terminal SHP2-interacting domains containing crucial Tyr phosphorylation sites (Tyr-627 and -659) (7,8,14,15) (Fig. 8b).…”
Section: The Gab1 Adaptor Is Both Stress-degraded and Caspasecleaved mentioning
confidence: 99%
“…Consistent with the increase in copy number gain at 8q observed in GAB2 overexpressing tumors, the protein with the most significant association with GAB2 overexpression was c-Myc (P ¼ 3.9 Â 10 À5 , ANOVA of RPPA data using GAB2 high-versus low-expressing tumors as defined above). Previous studies have suggested that GAB2 functions as a scaffold to facilitate activation of pathways downstream of a receptor tyrosine kinase, such as the PI3K pathway (21). We assessed whether elevated GAB2 expression correlated with downstream activation of the PI3K pathway by TCGA RPPA protein levels of pAKT-473, pAKT-308, and pPRAS40-246.…”
Section: Gab2 Copy Number and Overexpression Correlates To Protein Lementioning
confidence: 99%
“…Therefore, GAB1-targeted anti-cancer therapies could be more efficacious by blocking oncogenic signaling mediated by individual receptor kinases and their crosstalk. Strategies to target GAB1 and other docking proteins have been proposed (15,37).…”
Section: Discussionmentioning
confidence: 99%